Critical Review of Research Methods Used to Consider the Impact of Human–Animal Interaction on Older Adults' Health. (12th April 2018) - Friedmann, Erika; Gee, Nancy R
Abstract: Background and Objectives: Most research on human-animal interaction (HAI) and human health focuses on one of three perspectives: (a) health effects of pet ownership; (b) health effects of contact with a companion animal; or (c) health effects of animal-assisted interventions including animal-assisted therapies, and animal-assisted activities. Methods: We reviewed research methods used to address each perspective, within the context of human aging, and identified challenges associated with these methods. Results: The complex challenges involved in designing studies to address all three perspectives and examples of research design elements that can be used to alleviate issues raised in each type of study are provided. Discussion and Implications: We suggest emerging methodologies that may be helpful for answering important questions from all three perspectives about the relationship of HAI to health outcomes for older adults.